Growth Potential of Mangrove Crab (Scylla serrata) in Mantehage Island Waters, Bunaken National Park, North Sulawesi (Jurnal Ilmiah PLATAX, 2015)
Scylla serrata is one of the dominant muddy crabs caught in Mantehage Island coastal waters, North Sulawesi. The study was aim to determine the temporal distribution of S. serrata condition i based on carapace length - weight relationship and its condition factors. Data carapace width and weight of muddy crabs collected by enumerators from Oktober 2014 to April 2015. The results showed that b value of male (2.219 – 2.835) and female (1.264-2.352) were significantly different (P